Assessment of sCD14 levels in patients with endodontic pathology requiring root canal treatment: sCD14 levels in patients with endodontic pathology - Janani, Krishnamachari; Ajitha, Palanivelu; Teja, Kavalipurapu Venkata; Sandhya, Raghu (Brazilian Dental Science, 2022)
Objective: Dental caries is one of the most common microbial diseases. Because of the infectious nature of the disease, the immunologic response by the host plays an essential role in its development. Therefore, the aim of this study was to evaluate the sCD14 levels in patients exhibiting two to three teeth with caries involving pulp along with apical periodontitis requiring root canal treatment. Material and Methods: This study was carried out on 20 participants, of whom 10 were caries-free (Control) and 10 had two to three teeth with symptomatic irreversible pulpitis along with apical periodontitis requiring root canal treatment, within the ages of 20- 30 years. Unstimulated saliva of the participants was collected with disposable needleless syringe from buccal and labial vestibules. The sCD14 levels in salivary samples were assessed before and following endodontic treatment. The results were analyzed by ELISA. Results: The obtained levels of sCD14 were analyzed statistically. Paired T test was performed to assess the significance. The results revealed that there was a significant difference in sCD14 levels with a P=0.0005, as it had drastically reduced once the inflammation has subsided. Conclusion: Higher values of sCD14 levels were seen in patients with symptomatic irreversible pulpitis along with apical periodontitis than in caries free group. The study also showed that sCD levels were significantly reduced following post endodontic treatment. Therefore, increased levels of sCD14 can be considered as a marker of inflammation. KEYWORDS Dental caries; Apical periodontitis; Dental caries; ELISA; sCD14.